Enhancing English Learning Motivation of Madrasah Tsanawiyah EFL Teacher Trainees through Gamification-based Training Using the Wayground Digital Platform - Hanafi Pelu; Risna Risna; Sipa Pelu (Universitas Uluwiyah Mojokerto, Indonesia., 2026)
Low learning motivation in English language training for Madrasah Tsanawiyah (MTs) teachers is often caused by monotonous conventional methods. This study aims to analyze the improvement of participants' learning motivation through the implementation of gamification using the Wayground digital platform at the Makassar Religious Training Center. Using descriptive qualitative methods, data were collected through participant observation and in-depth interviews with training participants. The results showed that the use of game elements such as challenges, points, and leaderboards significantly changed participants' passive behavior to become more proactive and enthusiastic. Despite technical challenges such as variations in digital literacy and network stability, the instant feedback feature on Wayground successfully reduced language anxiety and increased participants' self-efficacy. Theoretically, this platform creates a flow state that supports adult learning autonomy (andragogy). In conclusion, digital gamification is effective as a motivational catalyst in religious training. It is recommended for training institutions to strengthen their digital infrastructure and the capacity of Widyaiswara (teacher instructors) in managing innovative content so that the digital transformation of training can be sustainable